A Critical Review of Performance-based Contract in Aerospace Industry - Cheong, Kai Yuan (2017)
This is the work of a critical literature review for performance-based contract in the aerospace industry. The research is separated into two different parts, namely, qualitative and quantitative review and analysis. The qualitative reviews and analysis covered the domains of servitization, performance-based contract and aircraft maintenance, repair and overhaul service. Servitization served an important market sector to the emergent of performance-based contract. Subsequently, such concept is introduced to the aerospace space industry and yielded successful results. The quantitative reviews and analysis are done to offer guidance into the diverse modelling method used for performance-based contracting practices where previously not done before. The models are analysed together to draw direct comparison between one another and discussion are conducted to point the advantages and also the deficient in each model. This research contribute to the understanding of performance-based contract from both qualitative and quantitative understanding.